PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN - Ning Setiyowati (Universitas Negeri Medan, 2022)
Abstract: Application of Project Based Learning to Improve Vocational High School Student Learning Outcomes. This study aims to improve student learning outcomes or achievements in implementing and operating presentation applications based on the Project Based Learning model. The research model used is Classroom Action Research (CAR) which adopts the model from Kemmis and McTaggart which includes planning, action, observation and evaluation activities. The research was carried out in class X SMK Negeri 1 Wonosari in the even semester of the 2020/2021 school year. The number of students involved were 36 people. Student learning outcomes are viewed from 3 indicators, namely test scores, PP application development scores, and presentation scores. All data on student learning outcomes were analyzed descriptively. The results of the action research obtained an increase in student learning outcomes for 2 cycles. Student test scores increased by 31.5%, application development scores increased by 30.7%, and presentation scores increased by 5.6%. After taking action in cycle 1, the number of students who achieved completeness was 100%. So, it can be concluded that learning using the PjBL model can improve the learning outcomes of class X students at SMK Negeri 1 Wonosari. Keywords: Project-Based Learning, Learning Outcomes, Classroom Action Research Abstrak: Penerapan Project Based Learning untuk Meningkatkan Hasil Belajar Siswa Sekolah Menengah Kejuruan. Penelitian ini bertujuan untuk meningkatkan hasil atau prestasi belajar siswa dalam menerapkan dan mengoperasikan aplikasi presentasi berdasarkan model Project Based Learning (PjBL). Model penelitian yang digunakan Penelitian Tindakan Kelas (PTK) yang mengadopsi model dari Kemmis dan McTaggart yang meliputi kegiatan perencanaan, tindakan, pengamatan dan evaluasi. Penelitian dilaksanakan di kelas X SMK Negeri 1 Wonosari semester genap tahun pelajaran 2020/2021. Jumlah siswa yang terlibat sebanyak 36 orang. Hasil belajar siswa ditinjau dari 3 indikator yaitu nilai tes, nilai pengembangan aplikasi PP, dan nilai presentasi. Seluruh data hasil belajar siswa dianalisis secara deskriptif. Hasil penelitian tindakan diperoleh adanya peningkatan hasil belajar siswa selama 2 siklus. Nilai tes siswa meningkat sebesar 31.5%, nilai pengembanagan aplikasi meningkat sebesar 30.7%, dan nilai presentasi meningkat sebesar 5.6%. setelah dilakukan tindakan pada siklus 1 diperoleh jumlah siswa yang mencapai ketuntasan sebesar 100%. Jadi, dapat disimpulkan bahwa pembelajaran menggunakan model PjBL dapat meningkatkan hasil belajar siswa kelas X SMK Negeri 1 Wonosari. Kata kunci: Project Based Learning, Hasil Belajar, Penelitian Tindakan Kelas